Osteosarcoma Diagnosis, Mechanisms, and Translational Developments - Gregory Cable, Matthew; Lawrence Randall, Robert (IntechOpen, 2019)
This book is titled Osteosarcoma - Diagnosis, Mechanisms, and Translational Developments, and focuses on recent advancements and novel ideas in osteosarcoma research. In a manner of speaking, we have taken the multidisciplinary mindset essential for treating osteosarcoma and broadened it to include other areas of cancer research. By learning from gains in other areas of oncology, such as new lncRNAs, the understanding of cancer metabolism and oxidative phosphorylation, and new chemotherapy agents, we can apply them to the niche of osteosarcoma for treatment development. By drawing more attention to these novel and clever discoveries, we hope to continue this enthusiasm for advancements in basic and translational research in the field of osteosarcoma.